A simple and cost-effective synthesis of ionic porous organic polymers with excellent porosity for high iodine capture. (9th September 2020) - Li, Zhongping; Li, He; Wang, Dongjin; Suwansoontorn, Athchaya; Du, Gang; Liu, Zhaohan; Hasan, Md Mahmudul; Nagao, Yuki
Abstract: Porous organic polymers (POPs) are excellent adsorbent candidates owing to their high porosity, permanent pore, and well-designed structure. Ionic porous organic polymers (i-POPs) are a special type of POPs, which can greatly improve the capacity of guest molecules through electrostatic interactions. However, most reported i-POPs have shortcomings such as low porosity and high-cost synthesis procedure. With these considerations in mind, several ionic porous organic polymers (i-POP-BP-BPTMs) have been successfully designed and synthesized by using the commercial and simple-synthesized building units via a simple and cost-effective process. i-POP-BP-BPTMs indicated excellent porosity including the highest BET surface area (1491–1753 m 2 g −1 ) and the best pore volume (2.19–2.94 cm 3 g −1 ) among most reported ionic POPs. Interestingly, i-POP-BP-BPTM was found to be highly effective in iodine vapor capture up to 415 wt%, which is higher than the value of all reported ionic POPs. These results offer a new way to design and construct functional ionic POPs. Graphical abstract: Image 1 Highlights: The i-POPs have been synthesized via a simple and cost-effective process. The i-POPs showed the highest BET surface area and pore volume. The i-POPs exhibited the best iodine uptake value among all reported ionic POPs. The capture process could be efficiently recycled and reused for five cycles.